A comparative study on the relationship between social networking site use and social capital among Australian and Korean youth. (20th October 2016) - Lee, Jee Young; Park, Sora; Na, Eun-Yeong; Kim, Eun-mee
ABSTRACT: Social network sites (SNS) have become increasingly pervasive in the daily lives of adolescents. This study explores the relationship between SNS use and perceived online social capital among adolescents using survey data from Australia and Korea. We conducted a face-to-face survey of adolescents (12–15-year-olds) in major cities in Australia ( N  = 401) and Korea ( N  = 644) in 2013. There was no significant difference in time spent on SNS between adolescents in the two countries; however, significant differences in the way adolescents use SNS were found. Australian adolescents tended to use SNS for group activities, whereas Koreans used it for social monitoring. There was a positive relationship between SNS use and online social capital in both countries. However, the types of social capital that were found to have a strong relationship to SNS use were different. Among Australian adolescents, SNS activities had a higher correlation with bonding social capital compared to bridging capital, whereas the result was contrasting among Korean adolescents. The impact of SNS use on online social capital differed between the two countries, showing that Australian adolescents reporting low SNS use gained online social capital if they used SNS more intensely. Finally, the impact of SNS use and culture on perceived online social capital was examined by conducting hierarchical multiple regressions. Interpersonal communication and group activities emerged as significant predictors of online social capital.